Pemberdayaan Siswa Madrasah Aliyah Negeri (MAN) 2 Banyumas dalam Upaya Peningkatan Kesehatan Reproduksi dan Pencegahan Penyakit Menular Seksual - Afifah Afifah; Rani Afifah Nur Hestiyani; Gema Citra Dwiputranti; Tri Okmawati Handini (Jurnal Pengabdian Pada Masyarakat, 2018)
THE EMPOWERMENT OF MADRASAH ALIYAH NEGERI 2 BANYUMAS STUDENTS TO IMPROVE THE REPRODUCTIVE HEALTH AND PREVENTION OF SEXUAL TRANSMITTED DISEASE. The incidence of pregnancy without marriage in students tens to increase. About 62.7% of teenagers in Indonesia have free sex and 21% who are pregnant have an abortion. About 30% of HIV-AIDS patients are teenagers. Knowledge of the importance of reproductive health, especially related to the way of transmission of sexually transmitted disease can help adolescents in making decisions of their health. Mandrasah Aliyah Negeri (MAN) 2 Banyumas is one of senior high school in center of city which were their students can access the information from either internet or mass media easely, so the tendency to access negative things that can affect theit actions is very possible. This empowerment was carried out with transfer knowledge, providing modules, leaflet, watch the video, and role play. The subject were 392 students of MAN 2 Banyumas. Pre-test and post-test score analyzed with wilcoxon sign-rank test. There were significant differences in students’ knowledge before and after the activity. In conclusion, this program can improve the knowledge of reproductive health and prevent the transmission of sexual transmitted disease in students of MAN 2 Banyumas.